Training task-selection skills: The effect of prompts and explicit instruction on transfer - Pieplenbosch, Jane; van den Broek, Gesa; Hoogerheide, Vincent; van Gog, Tamara (John Wiley and Sons Ltd, 2024)
For effective self-regulated learning with problem-solving tasks, students must accurately assess their performance and select a suitable next learning task. However, most students struggle with this. Recent research shows that self-assessment and task-selection skills can be trained through video modeling examples (SATS-training). However, the limited research available suggests that students struggle to transfer trained task-selection skills to other problem-solving contexts. We investigated whether guidance in the form of prompts (stating that the task-selection procedure can be adapted and used) or explicit instruction (on how the procedure can be adapted) would improve task-selection accuracy on transfer tasks with this guidance available and on later, unguided transfer tasks. Explicit instruction significantly enhanced task-selection accuracy compared to prompts and a no-guidance control condition on guided transfer tasks, but not on unguided transfer tasks. Thus, it remains a question how to lastingly improve transfer of task-selection skills also in the absence of guidance.
Keywords: example-based learning; self-regulated learning; STEM; task-selection; transfer; Experimental and Cognitive Psychology; Developmental and Educational Psychology; Arts and Humanities (miscellaneous)